Is Physical Performance a Differentiating Element between More or Less Successful Football Teams? - Jose Antonio Asian Clemente; Bernardo Requena; Igor Jukic; Jack Nayler; Alfredo Santalla Hernández; Christopher Carling (MDPI AG, 2019)
This study investigated the time-motion characteristics of football teams in the Spanish first division, in relation to their final competitive level as defined by league position (Champions League, Europa League, Upper mid-table, lower mid-table and relegation). Match observations (n = 9641) were collected using a multiple-camera computerized tracking system during the 2013−2014 competitive season. The following match parameters were analyzed: total distance, relative distance (m·min−1), distance < 14 km·h−1, >14 km·h−1, between 14−21 km·h−1, >21 km·h−1, and >24 km·h−1. Total distance and distance at different velocities (>14, 21, and 24 km·h−1) in and out of ball possession were also analyzed. A repeated analysis of variance and a comparison of effect sizes were carried out to compare the performance of the teams. The analysis of the data showed differences in physical performance characteristics between competitive levels. The volume of distance covered in the variables analyzed did not relate to success in soccer. Both successful and unsuccessful teams presented the same running requirements at higher velocities. These findings provide valuable information about the physical demands of the running requirements according to their final position in the league table.